(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article examines the logic of the development of philosophical anthropology in the context of classical and post-classical philosophy. In particular, the method of representation reproduces the concepts of Socrates, Plato, Aristotle, classical philosophy (I.Kant, D. Vico, H. Wolf, P. Holbach, J. Lammetry) postclassical philosophy (E. Husserl, M. Heidegger, Z. Freud, E. Fromm). Philosophical anthropology as an independent field of knowledge arises in the context of the general turn of philosophy at the end of the XIX – early XX century from epistemology and logic to ontology and anthropology; its ideas are present in a wide variety of philosophical directions and systems, regardless of which problem is decisive in them: ontological, logical